BIROKRATISASI PENEGAKAN HAK ASASI MANUSIA PASCA REFORMASI MELALUI PEMBENTUKAN KEMENTERIAN URUSAN HAM DAN PENGUATAN KOMNAS HAM - Arasy Pradana A Azis (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2019)
ABSTRACTThe Reformation then became a momentum for improving the issues of upholding human rights in Indonesia, where human rights matters formally entered into the division of power. On the one hand, for the first time, a ministry was formed specifically to deal with human rights matters. While outside the executive body, Law No. 39 of 1999 strengthens the position of the National Commission of Human Rights which has actually been established since 1993. This phenomenon then raises a problem statement, on how bureaucratization of human rights after Reformation is manifested through the establishment of the National Human Rights Commission and the Ministry of Human Rights. It was found that each institution gained legitimacy from political dynamics in a more democratic public space. Between the state ministries for human rights and the National Commission of Human Rights, the principle of check and balances was carried out in their role as an organ of the Indonesian bureaucracy. On the one hand, the state minister for human rights is an extension of the executive's hand in managing human rights matters. As a counterweight, the National Human Rights Commission carries out the role of the state auxiliary bodies to monitor the government’s human rights work.Keywords:    Politic of Law, Bureaucratization, Human Rigths, Ministry of Law and Human Rights Affairs, National Commission of Human Rights. ABSTRAKPeristiwa Reformasi menjadi momentum perbaikan urusan penegakan HAM di Indonesia, di mana urusan HAM secara formal masuk ke dalam pembagian kekuasaan negara. Di satu sisi, untuk pertama kalinya dibentuk satu kementerian yang secara khusus menangani urusan HAM. Sementara di luar lembaga eksekutif, Undang-Undang Nomor 39 Tahun 1999 menguatkan kedudukan Komisi Nasional Hak Asasi Manusia yang sejatinya telah terbentuk sejak tahun 1993. Fenomena ini kemudian menimbulkan satu rumusan permasalahan, yaitu bagaimana birokratisasi urusan HAM pasca reformasi termanifestasi melalui pembentukan Komnas HAM dan kementerian urusan HAM. Ditemukan bahwa masing-masing lembaga memperoleh legitimasi dari dinamika politik di ruang publik yang lebih demokratis. Antara kementerian negara urusan HAM dan Komnas HAM kemudian menjalankan prinsip check and balances dalam menjalankan perannya sebagai organ birokrasi Indonesia. Di satu sisi, kementerian negara urusan HAM merupakan perpanjangan tangan eksekutif untuk mengurus urusan HAM. Sebagai penyeimbang, Komnas HAM menjalankan peran sebagai state auxiliary bodies guna mengawasi kinerja HAM pemerintah.Kata Kunci: Politik Hukum, Birokratisasi, Hak Asasi Manusia, Kementerian Urusan HAM, Komnas HAM.